Role of lestari in capacity building for ecosystem health research towards sustainable development - Mazlin Mokhtar, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
Institute for Environment and Development (LESTARI) was established in October 1994 within the framework of the Universiti Kebangsaan Malaysia to address the issues and needs of sustainable development, in recognition of the national and international needs to manage our environment and resources intelligently for the present and future generations; in conformity with the declaration of the Earth Summit in Rio de Janeiro of 1992. The mission of LESTARI is to generate knowledge to support the sustainable use and conservation of the environment through innovative, scientific and strategic capacity building programs. The institute seeks to provide a professional service to its clients by understanding their needs; forging strategic alliances between researchers and users; enhancing inter and multidisciplinary collaborations; responding to the changing demands, national goals and priorities; and utilizing our scientific and human resources efficiently. Malaysia has an immense endowment of biodiversity, food, energy, minerals, tourism and recreational opportunities which brings monumental management responsibilities for these resources. LESTARI's strategies and plans of action are designed to help meet this challenge. The capacity building endeavours at LESTARI encompasses research effort in cross-sectoral and sectoral research areas. This paper describes and assesses to a certain extent, the infrastructure available, and methods that are useful in achieving sustainable development of our resources and environment.